Modeling Dyadic Effects in the Associations Between Relational Uncertainty, Sexual Communication, and Sexual Satisfaction for Husbands and Wives - Theiss, Jennifer A. (Communication Research, 2011)
This study models the individual and dyadic associations between relational uncertainty, indirect communication about sexual intimacy, and sexual satisfaction within marital relationships. A sample of 220 married couples completed questionnaires about their sexual relationship, and hypotheses were tested using structural equation modeling (SEM). Results indicate that (a) relational uncertainty is positively associated with indirect communication about sexual intimacy for both husbands and wives, (b) indirect sexual communication is negatively associated with husbands’ and wives’ own sexual satisfaction, (c) husbands’ and wives’ sexual satisfaction and indirectness about sexual intimacy are positively associated, and (d) husbands’ and wives’ indirect communication about sexual intimacy are negatively associated with their spouse’s sexual satisfaction. The results are discussed in terms of their implications for understanding the dynamics of sexual intimacy within marriage.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjExNDAyMTg2